UPAYA HUKUM PENANGGULANGAN TINDAK PIDANA PERJUDIAN TOGEL OLEH KEPOLISIAN DI POLRESTA DENPASAR - Adi Widhiantara, I Ketut; Suardana, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
The meaning of gambling actually is changing. Some times viewed as a gamblingand in other place and time viewed as a non gambling. Rapid technological developmentsome times abused by user. For example hand phone in use for gambling via short massageservice (SMS). Therefore, this paper will describe why someone love to gambling togel.This paper also describe remedies that conducted by police to tackling gambling. Thisresearch using yuridical empirical method. This method use for describe and analyze thecause of gambling. Based on the results of research that is why someone lave to gamblingtogel because a few factor, like external factor and internal factor. Remedies that conductedby police to tackling gambling such as preventive and repressive.
Keywords: Gambling, Remedies, factors